Enhanced Hardness in High‐Entropy Carbides through Atomic Randomness. Issue 9 (13th August 2020) - Wang, Yichen; Csanádi, Tamás; Zhang, Hangfeng; Dusza, Ján; Reece, Michael J.; Zhang, Rui‐Zhi
Abstract: High‐entropy carbides (HECs) are of great interest as they are promising candidates for ultra‐high‐temperature and high‐hardness applications. To discover carbides with enhanced yield strength and hardness, mechanism‐based design approaches are needed. In this study, dislocation core atomic randomness as a mechanism for hardness enhancement is proposed, in which the random interactions between different elements at a dislocation core make it more difficult for the dislocation to slip. The Peierls stress of an a / 2 ⟨ 1 1 ¯ 0 ⟩ 110 edge dislocation is calculated based on density functional theory, in which atomic randomness is increased by increasing the number of elements at the dislocation core. The results show that the Peierls stress statistically increases with increasing number of elements, indicating that incorporating more elements is likely to produce higher hardness. Based on this guiding principle, three eight‐cation HECs are fabricated (Ti, Zr, Hf, V, Nb, Ta, X, Y)C (X, Y = Mo, W, Cr, Mo, or Cr, W), the composition of which is guided by ab initio calculations of their formation enthalpy and entropy forming ability. The single‐phase dense ceramics all show high nanoindentation hardness of around 40 GPa. The random interactions between different elements at a dislocation core provide a mechanism for improving the hardness of structural ceramics. Abstract : Dislocation core atomic randomness in high‐entropy carbides is proposed as a mechanism for hardness enhancement. Density functional theory calculations show that it becomes more difficult to slip a dislocation with an increasing number of different elements at the dislocation core. Eight‐cation high‐entropy carbides are fabricated to verify this. Their nanoindentation hardness is around 40 GPa threshold for superhard materials.